Birds - Andrew Alek, Anak Tuen; Mohd-Azlan, Jayasilan; Chong, Yee Ling; Lit, H.D.E; Jimbai, J.; Rosedy, R.; Nurqamareena, K.; Yeo, S. T.; Balang, M.B.; Sim, L. K. (Natural History Publications (Borneo) Sdn. Bhd., Kota Kinabalu, UNIMAS Publisher, Sarawak Forestry Corporation Sdn Bhd, Kota Samarahan, 2018)
The Santubong Peninsula is dominated by the 810 m high Gunung Santubong. Early seafarers would have seen this sandstone mountain beckoning from afar and used it as a landmark to access, via Sarawak River, the hinterlands of Kuching. One famous visitor and probably the frst to collect birds from Santubong peninsula was Alfred Russel Wallace, who arrived in Sarawak on 1 November 1854, at the invitation of James Brooke, the frst Rajah of Sarawak. Writing in The Malay Archipelago, Wallace said he collected “from Santubong at its mouth up to the picturesque limestone mountains and Chinese gold-felds of Bow and Bede”. Wallace, however, was disappointed with his Sarawak bird collection of about 100 species. In the post-Wallace’s era, avifauna research and collection at Santubong slowed signifcantly until about 1997 when UNIMAS staff and students conducted a mist-netting survey from the foothills to the summit of Gunung Santubong (Tuen et al., 2000). This survey netted a total of 28 species and 118 individuals of understorey and ground level birds. The most abundant species were Rufous-tailed Tailorbird (Orthotomus sericeus), White-chested Babbler (Trichastoma rostratum), Little Spiderhunter (Arachnothera longirostra) and Cream-vented Bulbul (Pycnonotus simplex); together, these four species represented 50.8% of all the birds captured.